2002
DOI: 10.1075/eurosla.2.06alh
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of English tense morphophonology by advanced L2 speakers

Abstract: This study tests the assumption in much of the literature on the second language acquisition of English tense and aspect morphophonology (e.g. bare verbs, V-ing, V-ed) that once speakers are beyond intermediate levels of proficiency, both distribution and interpretation of these forms are represented in a target-like way in their mental grammars. Three groups of advanced non-native speakers (whose L1s were Chinese, Japanese and the verb-raising languages Arabic, French, German and Spanish) were compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that adult Japanese-speaking learners of English have difficulty with certain forms in specific contexts such as accepting -ing in a sentence like The plane is arriving at the airport when the context describes a completed event, i.e., a picture shows that the plane is stationary at the airport (Gabriele, 2009). Other difficulties for Japanese L2 learners relate to an over acceptance of -ing with verbs like know, e.g., *He is knowing him for many years (Al-Hamad et al, 2002;Hawkins et al, 2008). These studies suggest that difficulty results from influence of the -te iru form in Japanese, which superficially resembles the -ing form.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Previous studies have reported that adult Japanese-speaking learners of English have difficulty with certain forms in specific contexts such as accepting -ing in a sentence like The plane is arriving at the airport when the context describes a completed event, i.e., a picture shows that the plane is stationary at the airport (Gabriele, 2009). Other difficulties for Japanese L2 learners relate to an over acceptance of -ing with verbs like know, e.g., *He is knowing him for many years (Al-Hamad et al, 2002;Hawkins et al, 2008). These studies suggest that difficulty results from influence of the -te iru form in Japanese, which superficially resembles the -ing form.…”
Section: Introductionmentioning
confidence: 86%
“…They suggest that instruction and input are more likely to take precedence over L1 transfer as learners can interpret sentences like (17a) even if they have limited exposure to such sentences. In sum, the studies by Al-Hamad et al (2002), Hawkins et al (2008), and Okuwaki (2005) show that adult Japanese intermediate and advanced learners of English do have problems with achievement and stative verb types when they are asked to make judgments on present simple continuations vs. present progressive continuations of short contexts. Gabriele (2009) and Gabriele and Canales (2011) found that advanced Japanese learners can make correct judgments when such continuations are presented to learners in a short story.…”
Section: (15) Activity: Ongoing Contextmentioning
confidence: 91%
See 3 more Smart Citations